ANALISIS EFEKTIVITAS PENAGIHAN RETRIBUSI PERSAMPAHAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KOTA TOMOHON - Rembet, Juanda Elia; Tinangon, Jantje J.; Runtu, Treesje (Universitas Sam Ratulangi, 2018)
Regional Original Revenue (PAD) is regional revenue derived from local taxes, regional retribution, and management of separated regional assets, as well as other legitimate regional income. Regional levies are one of the sources of financing regional development in supporting the implementation of regional autonomy. One type of regional retribution collected by the Tomohon City Government is waste retribution. This study aims to analyze the effectiveness of waste collection fees in Tomohon City, and the contribution of solid waste retribution to PAD. In this study using quantitative descriptive method. The analysis data used in this study is the analysis of contribution and effectiveness. The results of the receipt effectiveness of solid waste levies in 2015-2016 was not effective and decreased, then in 2017 although it was still ineffective but experienced a very drastic increase. The contribution of solid waste retribution to regional retribution is still relatively small in 2015 and 2016 but in 2017 its contribution is very significant to regional retribution. While the contribution of solid waste retribution to the PAD of Tomohon City in 2015-2017 is very small for the past 3 years. Leaders of Regional Revenue Service and the Environmental Agency should continue to optimize the receipt of solid waste fees with intensification & extensification, so that there will always be changes on the system of receiving regional retribution towards a better direction.Keywords: effectivity, contribution, local government income